Peter Borscheid y Niels Viggo Haueter (Eds.). World Insurance: The Evolution of a Global Risk Network. Oxford, Oxford University Press, 2012, XVI+729 págs. - Wright, Robert E. (Investigaciones de Historia Económica, 2019)
Sin resumen